Employment dynamics in a rapid decarbonization of the US power sector - Bücker, J; del Rio-Chanona, RM; Pichler, A; Ives, MC; Farmer, JD (Cell Press, 2025)
We analyze the employment dynamics of a rapid decarbonization of the US power sector, reducing emissions by 95% before 2035. We couple an input-output model with an occupational mobility network and identify three labor market phases: “scale-up,” “scale-down,” and a long-term, low-carbon, “steady state.” During the scale-up (2023–2034), for every job lost in an industry, 12 new jobs are created elsewhere. However, few occupations see sustained growth throughout the transition. We predict that skill mismatches will create frictions during the transition, especially in the scale-down phase. Compared with the size and fluctuations of the US labor market, the impact of this transition is modest, particularly if the US increases exports of clean energy technologies to counteract the domestic scale-down phase. However, without proper planning, rapidly growing industries will struggle to find skilled labor during the scale-up phase, while displaced workers might struggle finding jobs during the scale-down phase.